THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT POS (PERSERO) POST OFFICE BEKASI 17000 - Ermita, Isyana; Syamsudin, Syamsudin; Sugeng, Irwin Sukrisno (AGUSPATI Research Institute, 2021)
This research is about the influence of organizational culture and works environment on employee performance at PT POS (Persero) Bekasi City 17000 to review the influence of organizational culture on the performance of employees of PT POS (Persero) Bekasi City 17000 and the influence of work environment on the performance of PT POS employees ( Persero) Kota Bekasi 17000. This research is categorized in survey research, by taking data using a questionnaire (questionnaire). This study is a population study with 77 respondents. Test the validity of the instrument using Pearson Product Moment, reliability test using Cronbach Alpha with the help of SPSS Version 24 Software. The analysis technique used is multiple linear regression with a significance level of 5%. The results show that: (1) Organizational culture has a significant positive effect on employee performance with (Î²) 0.684 and a significance level of 0.000. (2) The work environment has no significant positive effect on employee performance with (Î²) 0.132 and a significance level of 0.212. (3) Organizational culture and work environment simultaneously have a significant positive effect on employee performance with a significance level of 0.000